Makna Filosofis Dalam Secangkir Kopi Kehidupan - Robingun Suyud El Syam; Muhamad Yusuf Amin Nugroho (Journal of Creative Student Research, 2023)
The research intends to reveal the philosophical meaning in a cup of coffee of life, with a descriptive qualitative approach. After discussing and analyzing concluded; Coffee is a drink for all people. A connoisseur can know the existence of God from a cup of coffee, that in the fragrant aroma and delicious taste there are signs of the Kauniyah, the majesty of God. In front of connoisseurs, a cup of coffee never chooses who has the right to drink it. Likewise God, all servants before Him are the same, except piety. However delicious coffee must have a bitter side, but delicious coffee is bigger than the bitter side. Along with the bitter side of coffee, there are various tastes, that God has the nature of Jamaliyah (beauty). A cup of delicious coffee consists of various compositions: coffee, sugar and water, that enjoyment can be achieved because there are differences, life with differences is a blessing. Enjoy coffee when it's still warm, not hot or cold. Likewise religion, understanding religion must be precise and in context, not excessive. Peace, harmony, and unity are the teachings and commandments of God. That is one sign of God's greatness shown through coffee.